2020
DOI: 10.1111/eip.13041
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in ADHD: Duration of untreated illness and its socio‐demographic and clinical predictors in a sample of adult outpatients

Abstract: Aim: To investigate the Duration of Untreated Illness (DUI) and its sociodemographic and clinical predictors in a sample of adult ADHD outpatients. Methods:The DUI of 150 adult outpatients with a confirmed diagnosis of DSM-IV ADHD was calculated. Non-parametric tests were used to evaluate differences in DUI among subgroups and to build a correlation matrix. Subsequently, a multiple linear regression model was performed.Results: The median DUI was 17 years (interquartile range [IQR] = 14). DUI was longer in emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Only over recent years, some authors have remarked the importance of underdiagnosis and untreated ADHD consequences in old adults and elderly people (56)(57)(58)(59). A recent epidemiological study conducted on a Swedish national register (56) has shown that ADHD persists in elderly taking along psychiatric and metabolic comorbidity (over nine and two-fold prevalence than subjects without ADHD, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Only over recent years, some authors have remarked the importance of underdiagnosis and untreated ADHD consequences in old adults and elderly people (56)(57)(58)(59). A recent epidemiological study conducted on a Swedish national register (56) has shown that ADHD persists in elderly taking along psychiatric and metabolic comorbidity (over nine and two-fold prevalence than subjects without ADHD, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 This incremental caregiver burden translates to One area of unmet need that may contribute to the large burden of ADHD is that the condition is commonly undiagnosed in adults, thus leaving symptoms untreated, which points to insufficiencies at both the patient and physician levels. 35,36 At the patient level, some adults may present with ADHD that was not diagnosed during childhood and thus may be more difficult to diagnose during adulthood because of changes in clinical presentation associated with age, such as adults' internalization of the typical hyperactivity symptoms. [35][36][37][38] In addition, adults may develop better compensation strategies to further mask recognizable symptoms of ADHD.…”
Section: Indirect Costsmentioning
confidence: 99%
“…35,36 At the patient level, some adults may present with ADHD that was not diagnosed during childhood and thus may be more difficult to diagnose during adulthood because of changes in clinical presentation associated with age, such as adults' internalization of the typical hyperactivity symptoms. [35][36][37][38] In addition, adults may develop better compensation strategies to further mask recognizable symptoms of ADHD. 38 ADHD among adults may also be undiagnosed because it is instead misdiagnosed as another comorbid condition; ADHD symptoms are often mistaken for those of mood and anxiety disorders or personality disorders, among others.…”
Section: Indirect Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detrimental outcomes are similar between adult and childhood ADHD ( Ginsberg et al, 2014 ), including negative physical health consequences such as obesity, smoking, asthma, migraines, emergency room visits, and injury-related insurance claims and accidental deaths ( Agnew-Blais et al, 2016 ; Catalá-López et al, 2022 ; Dalsgaard et al, 2015 ; Lundervold et al, 2019 ; Sadeghi-Bazargani et al, 2019 ); and poor socio-economical outcomes such as higher chance to drop out of school ( Fleming & McMahon, 2012 ), financial problems from ADHD-associated impulsivity at work ( Asherson et al, 2012 ; Pinna et al, 2019 ) and increased chance to involve in criminal activities or live in detention centers ( Baggio et al, 2018 ). Despite the diagnostic challenges, accurate early diagnoses and appropriate treatment of ADHD could be effective to curb the negative outcomes ( Oliva et al, 2021 ).…”
mentioning
confidence: 99%